Jazz - Tanner, Paul O.W. 1917-2013; Megill, David W.; Gerow, Maurice (McGraw Hill, 1997)
"This outstanding introduction -- with an emphasis on listening -- provides you with an accessible and intriguing starting point for exploring the music, styles, and traditions of jazz."--Back cover